2008
DOI: 10.1021/ct800123c
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Molecular Polarizabilities Based on Continuum Electrostatics

Abstract: A novel approach for representing the intramolecular polarizability as a continuum dielectric is introduced to account for molecular electronic polarization. It is shown, using a finite-difference solution to the Poisson equation, that the Electronic Polarization from Internal Continuum (EPIC) model yields accurate gas-phase molecular polarizability tensors for a test set of 98 challenging molecules composed of heteroaromatics, alkanes and diatomics. The electronic polarization originates from a high intramole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 67 publications
(159 reference statements)
0
55
0
Order By: Relevance
“…After diagonalizing the static molecular polarizability tensor (computed via finite differences), the anisotropy of the polarizability can be measured by 119 Δα=12[(trueα~italicxxtrueα~italicyy)2+(trueα~italicyytrueα~italiczz)2+(trueα~italiczztrueα~italicxx)2]13(trueα~italicxx+trueα~italicyy+trueα~italiczz), where trueα~italicxx,trueα~italicyy and trueα~italiczz are the real part of the three components of the diagonalized polarizability tensor trueα~. The results calculated at the B3LYP/6-31G(d) level of theory are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After diagonalizing the static molecular polarizability tensor (computed via finite differences), the anisotropy of the polarizability can be measured by 119 Δα=12[(trueα~italicxxtrueα~italicyy)2+(trueα~italicyytrueα~italiczz)2+(trueα~italiczztrueα~italicxx)2]13(trueα~italicxx+trueα~italicyy+trueα~italiczz), where trueα~italicxx,trueα~italicyy and trueα~italiczz are the real part of the three components of the diagonalized polarizability tensor trueα~. The results calculated at the B3LYP/6-31G(d) level of theory are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One parameter of this method includes a solute’s dielectric constant. Tan et al assumed that a universal dielectric constant of 4 is optimal for all molecules tested; however, Truchon et al (2008) found that this value may depend on the class of molecules.…”
Section: Polarizable Force Fieldsmentioning
confidence: 99%
“…Truchon et al (2008) employed the continuum dielectric to develop a new approach for computing gas-phase molecular polarizabilities based on a finite-difference solution to the Poisson equation. A molecule is treated as an entity with a high dielectric, which produces electronic polarization.…”
Section: Polarizable Force Fieldsmentioning
confidence: 99%
“…Some common polarization models are based on induced dipoles 3537 , Drude oscillators 38 , fluctuating charges 3942 , and continuum dielectric models 43,44 . In many cases, the polarizability parameters are fit to or tested against experimental or theoretical molecular dipole-dipole polarizability tensors.…”
Section: Introductionmentioning
confidence: 99%